Introducing The City’s Cultural Heritage to The Students of Elementary School Through Picture Story Book - Hariyanti, Rosana; Nurhayani , Ika; Rahmadhani , Kurnia; Asyifa, Nadhifa Luqyana Wati Cahya; Ramadhany , Nabila Shifa; Zahra, Aurell Denastha; Prameswari, Auryn Zahra Choirunnisa (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
This community service activity aims to introduce elementary school students to the cultural heritage of their city. The focus was on Kampung Kayutangan Heritage, a historically significant area located in the heart of Malang City. The approach involved writing and publishing a picture storybook about the Kayutangan Heritage, which was subsequently donated to Brawijaya Smart School (BSS). Following the donation, a storytelling session was conducted for the students. This initiative not only enhanced students' awareness of the cultural and historical significance of their local heritage but also fostered a sense of responsibility toward its preservation.